Catalytic cracking catalyst
By modifying ZSM-5 molecular sieves with inorganic phosphorus compounds of +1 valence state, the hydrothermal stability and cracking activity are enhanced, leading to improved propylene yield and low-carbon olefin selectivity in catalytic cracking processes.
Patent Information
- Application Number
- CN202310783167.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
Conventional ZSM-5 molecular sieves suffer from poor hydrothermal stability and low propylene yield due to phosphorus species forming large molecules that block pores, reducing their effectiveness in catalytic cracking processes.
The use of inorganic phosphorus compounds with a +1 valence state, such as hypophosphorous acid and ammonium hypophosphite, to modify ZSM-5 molecular sieves, enhancing the coordination with framework aluminum and improving hydrothermal stability and cracking activity.
The modified ZSM-5 molecular sieves exhibit improved hydrothermal stability, higher crystal retention, and enhanced cracking activity, resulting in increased propylene yield and low-carbon olefin selectivity.
Smart Images

Figure CN119215977A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalytic cracking catalyst, and more particularly to a catalytic cracking catalyst containing a Y-type molecular sieve and a phosphorus-modified ZSM-5 molecular sieve. Background Art
[0002] ZSM-5 molecular sieve is a medium-pore molecular sieve with high silicon three-dimensional straight channels and MFI structure developed by Mobil Oil Company of the United States (USP3702886). Its unique pore structure gives it good shape-selective catalytic and isomerization performance. It also has the characteristics of high thermal and hydrothermal stability, high specific surface area, wide range of silicon-aluminum ratio, unique surface acidity and low carbon deposition. ZSM-5 molecular sieve is widely used as a catalyst and catalyst carrier, and has been successfully used in production processes such as alkylation, isomerization, disproportionation, catalytic cracking, methanol to gasoline, and methanol to olefins.
[0003] Since 1983, ZSM-5 molecular sieve has been used in catalytic cracking as an octane number aid for catalytic cracking, aiming to improve the octane number of catalytic cracking gasoline and the selectivity of light olefins. USP3758403 first disclosed the use of ZSM-5 as an active component for increasing propylene production, that is, ZSM-5 and REY were used together as active components to prepare FCC catalysts. USP5997728 discloses the use of ZSM-5 molecular sieve as an aid for increasing propylene production, and the molecular sieve is not modified in any way. However, the propylene yields of the above two technologies are not high. Although HZSM-5 molecular sieve has good shape selectivity and isomerization performance, its disadvantage is that it has poor hydrothermal stability and is easily deactivated under harsh high-temperature hydrothermal conditions, and its catalytic performance is reduced.
[0004] In the 1980s, Mobil Corporation discovered that phosphorus can improve the hydrothermal stability of ZSM-5 molecular sieves, and phosphorus modification of ZSM-5 molecular sieves increases the yield of light olefins. Conventional ZSM-5 additives activated with phosphorus are usually used to selectively convert primary cracking products (such as gasoline olefins) into C3 and C4 olefins. ZSM-5 molecular sieves are modified by introducing an appropriate amount of inorganic phosphorus compounds after synthesis, which can stabilize the framework aluminum under harsh hydrothermal conditions.
[0005] CN1211469A discloses a five-membered ring molecular sieve composition for producing more propylene and ethylene, which is composed of 85-95% by weight of a five-membered ring molecular sieve, 2-10% by weight of phosphorus calculated as oxide, 0.3-5% by weight of alkaline earth metal calculated as oxide, and 0.3-5% by weight of transition metal element calculated as oxide. The composition is used for catalytic thermal cracking reaction to obtain a higher ethylene yield.
[0006] The phosphorus-modified ZSM-5 molecular sieve disclosed in USP5171921 has a silicon-aluminum ratio of 20-60. After being impregnated with a phosphorus-containing compound and treated with steam at 500-700°C, it has higher activity when used for the reaction of converting C3-C20 hydrocarbons into C2-C5 olefins than HZSM-5 that has not been treated with phosphorus.
[0007] CN102166533A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises adding the molecular sieve to a phosphorus-containing aqueous solution, reacting for a period of time at a certain pH value, temperature and pressure, and then filtering, drying and calcining to obtain the phosphorus-modified molecular sieve; then adding the phosphorus-modified molecular sieve to an aqueous solution containing rare earth ions, reacting for a period of time at a certain temperature and pressure, and then filtering, washing, drying and calcining to obtain a composite modified molecular sieve. The composite modified molecular sieve is used to prepare a model catalyst, which has higher hydrothermal stability and micro-activity than the unmodified molecular sieve model catalyst and the molecular sieve model catalyst modified by other methods.
[0008] CN106994364A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises first mixing one or more phosphorus-containing compounds selected from phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate with a ZSM-5 molecular sieve having a high alkali metal ion content to obtain a mixture having a phosphorus loading of at least 0.1 wt% in terms of P2O5, drying and roasting the mixture, and then performing an ammonium crosslinking step and a water washing step to reduce the alkali metal ion content therein to below 0.10 wt%, and then undergoing drying and hydrothermal aging steps at 400-1000°C and 100% water vapor. The phosphorus-containing ZSM-5 molecular sieve obtained by the preparation method has a high total acid content, excellent cracking conversion rate and propylene selectivity, and also has a high liquefied gas yield.
[0009] Although the modification of ZSM-5 molecular sieves with organic / inorganic phosphorus-containing compounds can inhibit skeleton dealumination and thus improve hydrothermal stability, the introduction of phosphorus species also has the effect of regulating the properties of the acid center of the ZSM-5 molecular sieve, thereby improving the cracking conversion rate of long-chain alkanes and the selectivity of light olefins, phosphoric acid or ammonium phosphate will self-polymerize to form large molecular phosphorus species such as polyphosphoric acid due to dehydration during the calcination process, which are easily enriched on the outer surface of the molecular sieve, blocking the pores, reducing the pore volume and specific surface area, resulting in a low phosphorus-aluminum activation efficiency. After phosphorus modification, the ideal effect of improving hydrothermal stability cannot be achieved. Summary of the invention
[0010] The inventors found on the basis of a large number of experiments that the use of inorganic phosphorus compounds with a valence state of +1 and smaller molecules, such as hypophosphorous acid and ammonium hypophosphite, as phosphorus sources to treat ZSM-5 molecular sieves can promote the activation coordination of phosphorus and framework aluminum. The phosphorus-modified ZSM-5 molecular sieve obtained by the treatment has physical and chemical characteristics different from those of conventional phosphorus-containing ZSM-5 molecular sieves, and the phosphorus-aluminum stabilization efficiency of the molecular sieve is improved. In particular, in industrial applications, the hydrothermal stability, cracking activity and low-carbon olefin selectivity of the phosphorus-modified ZSM-5 molecular sieve after aging are improved. Based on this, the present invention is formed.
[0011] One of the purposes of the present invention is to overcome the problems of hydrothermal stability, cracking activity and low-carbon olefin selectivity in the prior art, and to provide a catalytic cracking catalyst based on a phosphorus-modified ZSM-5 molecular sieve different from the conventional one as one of the active components; the second purpose is to provide the application of the catalytic cracking catalyst in the catalytic cracking reaction of petroleum hydrocarbons.
[0012] In order to achieve one of the above-mentioned purposes, the first aspect of the present invention provides a catalytic cracking catalyst, which, based on the dry weight of the catalytic cracking catalyst, contains 2-20 wt% of a Y-type molecular sieve on a dry basis, 3-80 wt% of a phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70 wt% of an inorganic binder on a dry basis, and 2-60 wt% of clay on a dry basis, characterized in that the phosphorus-modified ZSM-5 molecular sieve has an electron binding energy of 134.2 to 134.3 eV in the surface phosphorus species after drying at 120° C. in the atmosphere of air during the preparation process, and after hydrothermal aging at 800° C. and 100% water vapor for 17 h, the binding energy of the phosphorus element in the phosphorus species on the surface of the molecular sieve is 134.6 to 134.7 eV and its 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10-25 ppm; the inorganic binder includes a phosphorus aluminum inorganic binder and / or other inorganic binders.
[0013] The binding energy of phosphorus in XPS characterization represents its chemical environment and valence state, which can explain the degree of polycondensation and valence state transformation of phosphorus species during drying and hydrothermal aging. The phosphorus-modified ZSM-5 molecular sieve described in the cracking catalyst of the present invention has an electron binding energy of 134.2-134.3 eV in the surface phosphorus species of the phosphorus-modified ZSM-5 molecular sieve after drying at 120°C in the atmosphere of air during the preparation process, and the binding energy of phosphorus is 134.6-134.7 eV after hydrothermal aging at 800°C and 100% water vapor. However, the phosphorus-modified molecular sieve of the prior art has almost no valence state transformation, so the binding energy of phosphorus after drying and aging is 134.8-134.9 eV.
[0014] 27 The chemical shift of the Al MAS-NMR spectrum is 39±3ppm. The resonance signal represents the framework aluminum species stabilized after coordination with the phosphorus species, that is, distorted tetracoordinated framework aluminum. The larger the half-peak full width of 39±3ppm, the more the number and types of framework aluminum stabilized by phosphorus, and the specific combination form of phosphorus and aluminum species may also be different. The phosphorus-modified ZSM-5 molecular sieve described in the cracking catalyst of the present invention is further subjected to hydrothermal aging at 800°C and 100% water vapor for 17 hours, and its 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3ppm is 10-25ppm, and preferably, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3ppm is 15-25ppm. In the prior art, the phosphorus-modified ZSM-5 molecular sieve modified with a phosphorus-containing precursor having a phosphorus valence of +5, such as diammonium hydrogen phosphate or phosphoric acid, has a full width at half maximum of 39ppm±3ppm of the resonance signal peak of 5-10ppm.
[0015] The phosphorus-modified ZSM-5 molecular sieve has a higher crystal retention (95% to 110%) after hydrothermal aging at 800°C and 100% water vapor for 17 hours, which also shows that the phosphorus species has a significant coordination effect with the framework aluminum, so that the framework aluminum is fully protected and the molecular sieve has excellent hydrothermal stability.
[0016] The phosphorus-modified ZSM-5 molecular sieve described in the cracking catalyst of the present invention has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
[0017] The phosphorus-modified ZSM-5 molecular sieve described in the cracking catalyst of the present invention is prepared by modifying the ZSM-5 molecular sieve with a phosphorus-containing compound having a phosphorus valence state of +1, including two methods: impregnation with an aqueous solution of a phosphorus precursor of +1-valent phosphorus and heating and melting treatment. For example, the HZSM-5 molecular sieve is impregnated with an aqueous solution of a phosphorus-containing compound having a phosphorus valence state of +1 at room temperature, such as 20-25°C, followed by drying and roasting; or the mixture obtained by mixing and grinding the HZSM-5 molecular sieve and a solid phosphorus-containing compound having a phosphorus valence state of +1 is subjected to heating and melting treatment, cooled to room temperature, such as 20-25°C, and then roasted.
[0018] One implementation method is to immerse the mixture in an aqueous solution with a water-to-screen weight ratio of 0.5 to 2 for 0.5 to 10 hours; the drying is carried out in an air atmosphere at 100 to 120° C. for 2 to 24 hours; and the calcination is carried out in an air atmosphere at 200 to 800° C. for 0.5 to 12 hours.
[0019] One embodiment is heating and melting treatment, the temperature is higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates (for example, the melting point of hypophosphorous acid is 26.5°C and the decomposition temperature is 130°C), and the treatment time is 2 to 72 hours.
[0020] The phosphorus-modified ZSM-5 molecular sieve described in the cracking catalyst of the present invention is obtained by treating the HZSM-5 molecular sieve with a phosphorus-containing compound having a phosphorus valence state of +1. By selecting a relatively small phosphorus source having a phosphorus valence of +1, the migration process of phosphorus species into the pores of the ZSM-5 molecular sieve is accelerated, and the activation efficiency of phosphorus-aluminum species is accelerated. The phosphorus-containing compound having a phosphorus valence state of +1 is selected from one or more of hypophosphorous acid, ammonium hypophosphite, and hypophosphite, or the phosphorus-containing compound aqueous solution having a phosphorus valence state of +1 is obtained by adjusting the pH value of hypophosphorous acid aqueous solution with ammonia water to 5-9. The phosphorus-containing compound having a phosphorus valence state of +1 is used as a phosphorus-containing precursor. After roasting, the phosphorus is converted from +1 to a higher oxidation valence state and has the conditions to stabilize the skeleton aluminum during the aging process. The molar ratio of the HZSM-5 molecular sieve to the phosphorus-containing compound with a phosphorus valence state of +1 is (0.1-2.5):1, preferably (0.5-1.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum and the phosphorus-containing compound is calculated as phosphorus. The HZSM-5 molecular sieve is obtained by reducing the sodium content of the ZSM-5 molecular sieve to <0.1wt% by ammonium exchange, and the silicon-aluminum ratio (molar ratio of silicon oxide to aluminum oxide, the same below) ranges from ≥10, usually from 10 to 200.
[0021] Regarding the phosphorus-modified ZSM-5 molecular sieve in the cracking catalyst of the present application, the present application also introduces the contents of the Chinese invention application with application number 202210884623.4 and application date July 26, 2022 for reference.
[0022] The Y-type molecular sieve described in the cracking catalyst of the present invention is at least one selected from PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.
[0023] In the catalyst of the present invention, preferably, the Y-type molecular sieve and the phosphorus-modified ZSM-5 molecular sieve account for 6-85% weight of the catalyst dry basis. Further, the Y-type molecular sieve on a dry basis accounts for 3-15% weight of the catalyst dry basis, and the phosphorus-modified molecular sieve on a dry basis accounts for 5-75% weight of the catalyst dry basis. More preferably, the weight ratio of the Y-type molecular sieve to the phosphorus-modified ZSM-5 molecular sieve is 1:(0.25-40).
[0024] In the catalyst of the present invention, the phosphorus-aluminum inorganic binder can be a phosphorus-aluminum inorganic binder and / or other inorganic binders. Based on the dry weight of the phosphorus-aluminum inorganic binder, the phosphorus-aluminum inorganic binder includes 15-40% by weight of aluminum component in terms of Al2O3, 45-80% by weight of phosphorus component in terms of P2O5, and its P / Al weight ratio is 1.0-6.0, the pH value is 1-3.5, and the solid content is 15-60% by weight; for example, it includes 15-40% by weight of aluminum component in terms of Al2O3, 45-80% by weight of phosphorus component in terms of P2O5; preferably, it contains 15-35% by weight of aluminum component in terms of Al2O3, 50-75% by weight of phosphorus component in terms of P2O5, and its P / Al weight ratio is preferably 1.2-6.0, more preferably 2.0-5.0, and the pH value is preferably 1.5-3.0. Preferably, the phosphorus-aluminum inorganic binder comprises 20-40 wt% aluminum component in terms of Al2O3 and 60-80 wt% phosphorus component in terms of P2O5, based on the dry weight. The phosphorus-aluminum inorganic binder can be prepared by the following steps: alumina source, clay (e.g., rectorite, kaolin) and water are slurried and dispersed into a slurry with a solid content of 5-50 wt%; wherein the alumina source is aluminum hydroxide and / or aluminum oxide (e.g., pseudo-boehmite, SB powder, γ-alumina) that can be peptized by acid, relative to 15-50 weight parts of the alumina source in terms of Al2O3; concentrated phosphoric acid is added to the slurry at a weight ratio of P / Al=1-6 under stirring, and the resulting mixed slurry is reacted at 50-99°C for 15-90 minutes; wherein P in P / Al is the weight of phosphorus in phosphoric acid in terms of elemental substance, and Al is the weight of aluminum in the alumina source in terms of elemental substance.
[0025] In the catalyst of the present invention, the other inorganic binder is selected from at least one of pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.
[0026] In the catalyst of the present invention, the clay is well known to those skilled in the art, and the clay may be at least one selected from kaolin, metakaolin, diatomaceous earth, sepiolite, attapulgite, montmorillonite and rectorite, preferably kaolin, metakaolin and rectorite. Based on the dry weight of the catalytic cracking catalyst, the catalytic cracking catalyst contains 2-60% by weight of clay on a dry basis, preferably 5-55% by weight of clay, and more preferably 15-40% by weight of clay.
[0027] In a specific preparation embodiment of the catalyst of the present invention, an inorganic binder (e.g., pseudo-boehmite, aluminum sol, silica sol, silica-alumina gel, or a mixture of two or more thereof) can be mixed with clay (e.g., kaolin) and water (e.g., deionized water and / or deionized water) to form a slurry with a solid content of 10 to 50% by weight, and stirred evenly. The slurry pH is adjusted to 1 to 4 with an inorganic acid such as hydrochloric acid, nitric acid, phosphoric acid, or sulfuric acid, and the pH value is maintained. After standing and aging at 20 to 80° C. for 0 to 2 hours, for example, 0.3 to 2 hours, aluminum sol and / or silica sol are added, stirred for 0.5 to 1.5 hours to form a colloid, and then a molecular sieve is added, the molecular sieve includes the phosphorus-modified ZSM-5 molecular sieve and the Y-type molecular sieve, to form a catalyst slurry, the solid content of the catalyst slurry is, for example, 20 to 45 weight%, and the stirring is continued and then spray-dried to form a microsphere catalyst. The microsphere catalyst is then calcined, for example, at 350-650°C or 400-600°C, preferably 450-550°C, for 0.5-6 hours or 0.5-2 hours, and then washed with ammonium sulfate (wherein the washing temperature can be 40-70°C, ammonium sulfate: microsphere catalyst: water = 0.2-0.8:1:5-15 weight ratio) until the sodium oxide content is less than 0.25% by weight, washed with water and filtered, and then dried.
[0028] In another specific preparation embodiment of the catalyst of the present invention, the Y-type molecular sieve and the phosphorus-modified ZSM-5 molecular sieve, the phosphorus-aluminum inorganic binder and other inorganic binders can be mixed, clay is added, slurried, and spray-dried.
[0029] In order to achieve the second objective mentioned above, the second aspect of the present invention provides a catalytic cracking method, which is to contact and react hydrocarbon oil with the catalytic cracking catalyst provided by the first aspect under catalytic cracking reaction conditions.
[0030] In the catalytic cracking method, the catalytic cracking catalyst can be added to the catalytic cracking reactor alone, for example, under catalytic cracking conditions, the hydrocarbon oil is contacted with the catalytic cracking catalyst of the present invention for reaction; or, the catalytic cracking catalyst can be used in a mixture with other catalytic cracking catalysts, and the catalytic cracking catalyst of the present invention can account for no more than 30% by weight of the total amount of the above mixture, preferably 1-25% by weight, and more preferably 3-15% by weight. The catalytic cracking catalyst of the present invention can be used for catalytic cracking of various hydrocarbon oils. The hydrocarbon oil can be selected from various petroleum fractions, such as crude oil, naphtha, catalytic gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight run wax oil, propane light / heavy deoiling, coking wax oil and coal liquefaction products. The hydrocarbon oil can contain heavy metal impurities such as nickel and vanadium and sulfur and nitrogen impurities, such as the sulfur content in the hydrocarbon oil can be as high as 3.0% by weight, the nitrogen content can be as high as 2.0% by weight, and the content of metal impurities such as vanadium and nickel can be as high as 3000ppm.
[0031] The catalytic cracking reaction conditions can be conventional in the art, including: the reaction temperature is 500-800°C, for example 550-680°C, and the hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue oil, vacuum residue oil, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products.
[0032] The catalytic cracking catalyst provided by the present invention contains a phosphorus-modified ZSM-5 molecular sieve with special physicochemical parameters; the phosphorus-modified ZSM-5 molecular sieve is obtained by selecting a relatively small molecular +1-valent phosphorus source for modification; the +1-valent phosphorus source accelerates the migration process of phosphorus species into the pores of the ZSM-5 molecular sieve, and accelerates the activation efficiency of phosphorus-aluminum species; the phosphorus species and the framework aluminum have obvious coordination effects, so that the framework aluminum is fully protected, and has a higher crystal retention (95% to 110%) after hydrothermal aging at 800°C and 100% water vapor for 17 hours, that is, it has excellent hydrothermal stability. The molecular sieve and the Y-type molecular sieve are used together as active components of the catalytic cracking catalyst, and have the characteristics of high cracking conversion rate, low carbon olefin yield, and high liquefied gas yield in the hydrocarbon oil catalytic cracking reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The phosphorus-modified ZSM-5 molecular sieve samples JCB-1 and DPB-1 in the cracking catalyst 27 Al MAS-NMR spectrum.
[0034] Figure 2 XPS (P2pScan) spectra of phosphorus-modified ZSM-5 zeolite samples JCB-1 and DPB-1 in cracking catalysts.
[0035] Figure 3 The phosphorus-modified ZSM-5 molecular sieve samples JCB-2 and DPB-3 in the cracking catalyst 27 Al MAS-NMR spectrum.
[0036] Figure 4 This is the XPS (P2p Scan) spectrum of the phosphorus-modified ZSM-5 molecular sieve sample JCB-2 in the cracking catalyst.
[0037] Figure 5 The phosphorus-modified ZSM-5 molecular sieve samples JNB-3 and DPB-5 in the cracking catalyst 27 Al MAS-NMR spectrum.
[0038] Figure 6 This is the XPS (P2p Scan) spectrum of the phosphorus-modified ZSM-5 molecular sieve sample JNB-3 in the cracking catalyst. DETAILED DESCRIPTION
[0039] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0040] X-ray diffraction (XRD) spectra were measured on a Rigaku TTR-3 powder X-ray diffractometer. Instrument parameters: copper target (tube voltage 40 kV, tube current 250 mA), scintillation counter, step width 0.02°, scanning rate 0.4 (°) / min. The ZSM-5 molecular sieve synthesized by the method of Example 1 in CN1056818C was used as a standard sample, and its crystallinity was set to 100%. The relative crystallinity is expressed as a percentage of the sum of the peak areas of the five characteristic diffraction peaks at 2θ between 22.5 and 25.0° of the X-ray diffraction spectra of the obtained product and the standard sample.
[0041] 27 Al MAS-NMR spectrum analysis was performed on a Bruker AVANCE III 600WB spectrometer. Instrument parameters: rotor diameter 4 mm, resonance spectrum 156.4 MHz, pulse width 0.4 μs (corresponding to 15° bevel angle), magic angle rotation speed 12 kHz, delay time 1 s. 27 The characteristics of the Al MAS-NMR spectrum are that the characteristic peak 1 at 54±3 ppm is attributed to the tetracoordinated framework aluminum, and the characteristic peak 2 at 39±3 ppm is attributed to the phosphorus-stabilized framework aluminum (distorted tetracoordinated framework aluminum). The area of each peak is calculated by the integration method after peak fitting of the characteristic peaks.
[0042] X-ray photoelectron spectroscopy (XPS) was used to analyze the molecular sieve surface and examine the migration of phosphorus compounds using the ESCALAB 250 X-ray photoelectron spectrometer from Thermo Fisher-VG. Instrument parameters: The excitation source was monochromatic AlKα X-ray with a power of 150 W, and the charge shift was corrected using the C1s peak (284.8 eV) from contaminated carbon.
[0043] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.
[0044] The properties of some of the raw materials used in the examples are as follows:
[0045] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight. Aluminum sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight. Silica sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with a SiO2 content of 28.9% by weight and a Na2O content of 8.9%.
[0046] The kaolin was kaolin for catalytic cracking catalyst produced by Suzhou Kaolin Company, with a solid content of 78% by weight. The rectorite was produced by Hubei Zhongxiang Mingliu Rectorite Development Co., Ltd., with a quartz sand content of <3.5% by weight, an Al2O3 content of 39.0% by weight, a Na2O content of 0.03% by weight, and a solid content of 77% by weight.
[0047] SB aluminum hydroxide powder, produced by Condex, Germany, has an Al2O3 content of 75% by weight.
[0048] HRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a rare earth content of 10% by weight. PSRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a Na2O content of <1.5% by weight, a P2O5 content of 0.8-1.2% by weight, a unit cell constant of <2.456nm, and a crystallinity of ≥64%.
[0049] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.
[0050] Examples 1-13 illustrate the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention and its preparation.
[0051] Example 1
[0052] Example 1 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0053] Take 6.9g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve sample is recorded as JCB-1.
[0054] Example 2
[0055] Example 2 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0056] 8.7 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-modified ZSM-5 molecular sieve sample was recorded as JNB-1.
[0057] Example 3
[0058] Example 3 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0059] Take 6.9g of solid hypophosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RCB-1.
[0060] Example 4
[0061] Example 4 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0062] 8.7 g of solid ammonium hypophosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature; the above sample was calcined at 550°C for 2 h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-1.
[0063] Comparative Example 1
[0064] Take 13.9g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-1.
[0065] Comparative Example 2
[0066] Take 12.1g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-2.
[0067] The XRD relative crystallinity and crystal retention of samples JCB-1, JNB-1, RCB-1, RNB-1, and comparison samples DPB-1 and DPB-2 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 1.
[0068] Sample JCB-1 and comparison sample DPB-1 27 Al MAS-NMR spectrum is shown in Figure 1 . Figure 1 The characteristic peak with a chemical shift of 39 ppm is attributed to the distorted four-coordinated framework aluminum formed by the combination of phosphorus and aluminum, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JCB-1 Figure 1 The features are the same.
[0069] The full width at half maximum of the characteristic peaks at chemical shift of samples JCB-1, JNB-1, RCB-1, RNB-1, and comparative samples DPB-1 and DPB-2 at 39 ppm are shown in Table 2.
[0070] The XPS (P2p Scan) spectra of sample JCB-1 and comparative sample DPB-1 are shown in Figure 2 In the figure, the peaks 134.2eV and 134.6eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-1 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-1 after hydrothermal aging at 800°C and 100% water vapor for 17 hours, respectively. 134.8eV and 134.9eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of the comparative sample DPB-1 after corresponding drying and hydrothermal aging, respectively. The XPS (P2p Scan) spectral characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples JNB-1, RCB-1, and RNB-1 after hydrothermal aging at 800°C and 100% water vapor for 17 hours are similar to those of sample JCB-1. Figure 2 The features are the same.
[0071] Table 1
[0072]
[0073] Table 2
[0074] sample 39ppm characteristic peak half-peak full width / ppm JCB-1 17 JNB-1 19 RCB-1 16 RNB-1 18 DPB-1 7 DPB-2 9
[0075] Example 5
[0076] Example 5 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0077] Take 3.45g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JCB-2.
[0078] Example 6
[0079] Example 6 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0080] Take 4.4g of ammonium hypophosphite and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JNB-2.
[0081] Example 7
[0082] Example 7 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0083] Take 3.45g of solid hypophosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C and a time of 10h. After the end, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RCB-2.
[0084] Example 8
[0085] Example 8 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0086] Take 4.4g of solid ammonium hypophosphite and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 40°C and a time of 10h. After the end, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-2.
[0087] Comparative Example 3
[0088] Take 6.95g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-3.
[0089] Comparative Example 4
[0090] Take 6.05g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-4.
[0091] The XRD relative crystallinity and crystal retention of samples JCB-2, JNB-2, RCB-2, RNB-2, and comparison samples DPB-3 and DPB-4 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 3.
[0092] Sample JCB-2 and comparative sample DPB-3 27 Al MAS-NMR spectrum is shown in Figure 3 In the figure, the characteristic peak with chemical shift at 39 ppm is attributed to the distorted four-coordinated framework aluminum formed after phosphorus and aluminum combine, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JCB-2 Figure 3 The features are the same.
[0093] The characteristic peak with chemical shift at 39 ppm for samples JCB-2, JNB-2, RCB-2, RNB-2, and comparative samples DPB-3 and DPB-4 is shown in Table 4.
[0094] The XPS (P2p Scan) spectrum of sample JCB-2 is shown in Figure 4In the figure, the peaks 134.3eV and 134.7eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-2 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-2 after hydrothermal aging at 800°C and 100% water vapor for 17h. The XPS (P2p Scan) spectrum characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples JNB-2, RCB-2, and RNB-2 after hydrothermal aging at 800°C and 100% water vapor for 17h are similar to those of sample JCB-2. Figure 4 The features are the same.
[0095] Table 3
[0096]
[0097] Table 4
[0098] sample 39ppm characteristic peak half-peak full width / ppm JCB-2 17 JNB-2 19 RCB-2 18 RNB-2 19 DPB-3 8 DPB-4 8
[0099] Example 9
[0100] Example 9 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0101] 13.02 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-containing ZSM-5 molecular sieve sample was recorded as JNB-3.
[0102] Example 10
[0103] Example 10 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0104] 13.02 g of ammonium hypophosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature. The above sample was calcined at 550°C for 2 h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-3.
[0105] Embodiment 11
[0106] Example 11 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention.
[0107] Take 10.35g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, add ammonia water to adjust the pH value of the solution to 5-9, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JCB-4.
[0108] Comparative Example 5
[0109] Take 20.85g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-5.
[0110] Comparative Example 6
[0111] Take 18.15g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-6.
[0112] The XRD relative crystallinity and crystal retention of samples JNB-3, RNB-3, JCB-4, and comparison samples DPB-5 and DPB-6 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 5.
[0113] Sample JNB-3 and comparative sample DPB-5 27 Al MAS-NMR spectrum is shown in Figure 5 In the figure, the characteristic peak with chemical shift at 39 ppm is attributed to the distorted four-coordinated framework aluminum formed after phosphorus and aluminum combine, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JNB-3 Figure 5 The features are the same.
[0114] The full width at half maximum of the characteristic peaks with chemical shifts at 39 ppm for samples JNB-3, RNB-3, JCB-4, and comparative samples DPB-5 and DPB-6 are shown in Table 6.
[0115] The XPS (P2p Scan) spectrum of sample JNB-3 is shown in Figure 6 In the figure, the peaks 134.3eV and 134.6eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-3 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-3 after hydrothermal aging at 800°C and 100% water vapor for 17h. The XPS (P2p Scan) spectrum characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples RNB-3 and JCB-4 after hydrothermal aging at 800°C and 100% water vapor for 17h are similar to those of sample JNB-3. Figure 6 The features are the same.
[0116] Table 5
[0117]
[0118]
[0119] Table 6
[0120] sample 39ppm characteristic peak half-peak full width / ppm JNB-3 19 RNB-3 20 JCB-4 19 DPB-5 7 DPB-6 9
[0121] Example 12
[0122] Example 12 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention, with a silicon-to-aluminum ratio of 100 and a phosphorus-to-aluminum ratio of 1.0.
[0123] 1.36 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=100) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-containing ZSM-5 molecular sieve sample was recorded as JNB-5.
[0124] Comparative Example 7
[0125] Take 2.16g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=100), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-7.
[0126] Example 13
[0127] Example 12 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention, with a silicon-to-aluminum ratio of 150 and a phosphorus-to-aluminum ratio of 1.0.
[0128] Take 0.91g of ammonium hypophosphite and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=150), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JNB-6.
[0129] Comparative Example 8
[0130] Take 1.45g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=150), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-8.
[0131] The XRD relative crystallinity and crystal retention of sample JNB-5, comparative sample DPB-7, JNB-6, and comparative sample DPB-8 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 7. 27 The full width at half maximum of the characteristic peak with a chemical shift of 39 ppm in the Al MAS-NMR spectrum is shown in Table 8.
[0132] The electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-5 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species after hydrothermal aging at 800°C and 100% water vapor for 17 hours are 134.2eV and 134.7eV, respectively.
[0133] The electron binding energies of the phosphorus element in the surface phosphorus species of the comparative sample DPB-7 after drying and hydrothermal aging are 134.8 eV and 134.9 eV, respectively.
[0134] The electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-6 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species after hydrothermal aging at 800°C and 100% water vapor conditions for 17 hours are 134.3eV and 134.6eV, respectively.
[0135] The electron binding energies of the phosphorus element in the surface phosphorus species of the comparative sample DPB-8 after drying and hydrothermal aging are 134.8 eV and 135.0 eV, respectively.
[0136] Table 7
[0137]
[0138] Table 8
[0139] sample 39ppm characteristic peak half-peak full width / ppm JNB-5 19 DPB-7 18 JNB-6 9 DPB-8 8
[0140] The phosphorus-aluminum inorganic binder used in the following examples is prepared by the following process:
[0141] 1. NJ1: 1.91 kg of pseudo-boehmite (containing 1.19 kg of Al2O3), 0.56 kg of kaolin (0.5 kg on a dry basis) and 3.27 kg of decationized water were slurried for 30 minutes, and 5.37 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring, with the phosphoric acid addition rate being 0.04 kg of phosphoric acid / min / kg of alumina source, and the temperature was raised to 70°C, and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder. The material ratio is shown in Table 9, and the sample number is NJ1.
[0142] 2. NJ2: According to the preparation process of NJ1, the material ratio is shown in Table 9, and the sample number is NJ2.
[0143] Table 9
[0144]
[0145] Examples 14-26 illustrate the catalytic cracking catalysts of the present invention.
[0146] Examples 14-17
[0147] Take the phosphorus-modified molecular sieve JCB-1, Y-type molecular sieve (PSRY molecular sieve), kaolin and pseudo-boehmite of Example 1, add decationized water and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, then add the phosphorus-aluminum inorganic binder NJ1, stir for 30 minutes, and then spray dry the obtained slurry to obtain microspheres. The microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered C1.
[0148] The molecular sieve JCB-1 was replaced by the phosphorus-modified molecular sieves JNB-1, RCB-1 and RNB-1 of Examples 2-4, respectively, and catalysts numbered C2, C3 and C4 were prepared by the same preparation process as above.
[0149] In the material proportions of C1, C2, C3 and C4, based on dry weight, phosphorus-modified molecular sieve accounts for 60%, PSRY accounts for 5%, kaolin accounts for 20%, phosphorus-aluminum binder NJ1 accounts for 10%, and pseudo-boehmite accounts for 5%.
[0150] Comparative Examples 9 and 10
[0151] The preparation process and material ratio are the same as those of Example 14, except that the phosphorus-modified molecular sieves DPB-1 and DPB-2 of Comparative Examples 1 and 2 are used to replace the molecular sieve JCB-1, to prepare comparative catalysts, numbered DC1 and DC2, respectively.
[0152] Examples 15-21
[0153] Take the phosphorus-modified molecular sieve JCB-2, Y-type molecular sieve (HRY molecular sieve), and kaolin of Example 5, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ2. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered C5.
[0154] The molecular sieve JCB-2 was replaced by the phosphorus-modified molecular sieves JNB-2, RCB-2 and RNB-2 of Examples 6-8, respectively, and the catalysts numbered C6, C7 and C8 were prepared by the same preparation process as above.
[0155] In the material proportions of C5, C6, C7 and C8, calculated on a dry basis, phosphorus-modified molecular sieve accounts for 60%, HRY accounts for 5%, kaolin accounts for 20%, phosphorus-aluminum binder NJ2 accounts for 10%, and aluminum sol accounts for 5%.
[0156] Comparative Examples 11 and 12
[0157] The preparation process and material ratio are the same as those of Example 15, except that the phosphorus-modified molecular sieves DPB-3 and DPB-4 of Comparative Examples 3 and 4 are used to replace the molecular sieve JCB-2, respectively, to prepare comparative catalysts, numbered DC3 and DC4.
[0158] Examples 22-24
[0159] Take the phosphorus-modified molecular sieve JNB-3, Y-type molecular sieve (PSRY molecular sieve), and kaolin of Example 9, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ1. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered C9.
[0160] The molecular sieve JNB-3 was replaced by the phosphorus-modified molecular sieves RNB-3 and JCB-4 of Examples 10-11, respectively, and the catalysts numbered C10 and C11 were prepared by the same preparation process as above.
[0161] In the material proportions of C9, C10 and C11, calculated on a dry basis, phosphorus-modified molecular sieve accounts for 50%, PSRY accounts for 20%, kaolin accounts for 15%, phosphorus-aluminum binder NJ1 accounts for 10%, and pseudo-boehmite accounts for 5%.
[0162] Comparative Examples 13 and 14
[0163] The preparation process and material ratio are the same as those of Example 22, except that the phosphorus-modified molecular sieves DPB-5 and DPB-6 of Comparative Examples 5 and 6 are used to replace the molecular sieve JNB-3, respectively, to prepare comparative catalysts, numbered DC5 and DC6.
[0164] Embodiment 25, 26
[0165] Take the phosphorus-modified molecular sieve JNB-5, Y-type molecular sieve (HRY molecular sieve) and kaolin of Example 12, add decationized water and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ1. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered C12.
[0166] The phosphorus-modified molecular sieve JNB-6 of Example 13 was used to replace the molecular sieve JNB-5, and the catalyst numbered C13 was prepared by the same preparation process as above.
[0167] In the material proportions of C12 and C13, based on dry weight, phosphorus-modified molecular sieve accounts for 60%, HRY accounts for 5%, kaolin accounts for 20%, and phosphorus-aluminum binder NJ1 accounts for 15%.
[0168] Comparative Example 15
[0169] The preparation process and material ratio are the same as those of Example 25, except that the phosphorus-modified molecular sieve DPB-7 of Comparative Example 7 is used instead of the molecular sieve JNB-5 to prepare a comparative catalyst, numbered DC7.
[0170] Comparative Example 16
[0171] The preparation process and material ratio are the same as those of Example 26, except that the phosphorus-modified molecular sieve DPB-8 of Comparative Example 8 is used instead of the molecular sieve JNB-6 to prepare a comparative catalyst, numbered DC8.
[0172] The following examples illustrate the catalytic cracking method provided by the present invention.
[0173] Examples 27-30
[0174] Catalytic cracking catalysts C1-C4 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were loaded into a fixed bed microreactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and a catalyst-to-oil ratio of 3.2.
[0175] The properties of the light hydrocarbon feedstock are shown in Table 10, and the results of the catalytic cracking reaction are shown in Table 11.
[0176] Comparative Examples 17 and 18
[0177] Same as Example 27, except that comparative catalysts DC1 and DC2 were used to replace C1. The catalytic cracking reaction results are shown in Table 11.
[0178] Table 10
[0179] project Light hydrocarbons <![CDATA[Density (20 °C) / (kg·m -3 )]]> 670.7 Element mass composition / % C 83.81 H 16.19 <![CDATA[S / mg.L -1 ]]> 2.6 <![CDATA[N / mg.L -1 ]]> <0.3 Distillation range / ℃ Initial distillation point 33.7 10% 56.3 30% 69.1 50% 86.6 70% 107.2 90% 130.5 95% 137.5 Final distillation point 155.7 Hydrocarbon mass composition / % Normal alkanes 72.69 Isoalkanes 25.48 Olefins 0.13 Cycloalkanes 1.56 Aromatics 0.17 total 100.03
[0180] Table 11
[0181] project Embodiment 27 Embodiment 28 Embodiment 29 Embodiment 30 Comparative Example 17 Comparative Example 18 Catalyst No. C1 C2 C3 C4 DC1 DC2 Conversion rate 66.54 68.06 65.04 67.13 61.31 60.10 Coke quantity 8.87 8.97 8.99 9.01 9.82 9.62 Liquid product yield / wt% 33.46 32.55 33.06 32.87 38.69 39.23 Gas product yield / wt% 57.67 58.48 57.95 58.12 51.49 51.15 Cracked gas product yield, wt% C2= 14.83 15.76 14.66 15.22 13.07 12.88 C3= 18.19 19.01 17.66 18.66 16.94 15.25
[0182] Examples 31-34
[0183] Catalysts C5-C8 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were loaded into a fixed bed microreactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and a catalyst-to-oil ratio of 3.2.
[0184] The catalytic cracking reaction results are shown in Table 12.
[0185] Comparative Examples 19 and 20
[0186] Same as Example 31, except that comparative catalysts DC3 and DC4 were used to replace C5. The catalytic cracking reaction results are shown in Table 12.
[0187] Table 12
[0188] project Embodiment 31 Embodiment 32 Embodiment 33 Embodiment 34 Comparative Example 19 Comparative Example 20 Catalyst No. C5 C6 C7 C8 DC3 DC4 Conversion rate 67.65 70.17 67.15 69.54 62.92 61.54 Coke quantity 10.61 11.02 10.23 11.59 12.61 13.03 Liquid product yield / wt% 30.25 28.38 31.06 29.07 29.55 29.23 Gas product yield / wt% 59.14 60.60 58.71 59.34 57.84 57.74 Cracked gas product yield, wt% C2= 15.30 16.11 14.96 15.92 13.71 13.66 C3= 19.71 21.04 19.01 20.66 17.34 16.92
[0189] It can be seen from Table 12 that the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +1 has an increased light hydrocarbon conversion rate, reduced coke, and improved ethylene and propylene yields compared to the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +5.
[0190] Examples 35-37
[0191] Catalysts C9-C11 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were loaded into a fixed bed microreactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and a catalyst-to-oil ratio of 3.2.
[0192] The catalytic cracking reaction results are shown in Table 13.
[0193] Comparative Examples 21 and 22
[0194] Same as Example 35, except that comparative catalysts DC5 and DC6 were used to replace C9. The reaction results are shown in Table 13.
[0195] Table 13
[0196] project Embodiment 35 Embodiment 36 Embodiment 37 Comparative Example 21 Comparative Example 22 Catalyst name C9 C10 C11 DC5 DC6 Conversion rate 56.11 53.78 56.03 49.72 48.84 Coke quantity 4.78 4.93 4.66 5.21 5.09 Liquid product yield / wt% 48.55 50.11 49.02 55.23 57.18 Gas product yield / wt% 46.67 44.96 46.32 39.56 37.73 Cracked gas product yield, wt% C2= 9.76 9.01 9.55 6.47 6.04 C3= 14.01 13.58 13.88 10.11 9.76
[0197] It can be seen from Table 13 that the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +1 has an increased light hydrocarbon conversion rate, reduced coke, and improved ethylene and propylene yields compared to the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +5.
[0198] Embodiment 38, 39
[0199] Catalysts C12 and C13 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were loaded into a fixed bed microreactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and a catalyst-oil ratio of 3.2.
[0200] The results of the catalytic cracking reaction are shown in Table 14.
[0201] Comparative Examples 23 and 24
[0202] Same as Example 38, except that comparative catalysts DC7 and DC8 are used to replace C12.
[0203] The results of the catalytic cracking reaction are shown in Table 14.
[0204] Table 14
[0205] project Embodiment 38 Embodiment 39 Comparative Example 23 Comparative Example 24 Catalyst name C12 C13 DC7 DC8 Conversion rate 48.77 46.22 45.16 42.81 Coke quantity 3.56 3.13 4.09 3.86 Liquid product yield / wt% 60.07 63.78 63.79 66.14 Gas product yield / wt% 36.37 33.09 32.12 30.00 Cracked gas product yield, wt% C2= 3.76 3.21 2.99 2.34 C3= 8.01 6.98 6.58 5.55
[0206] It can be seen from Table 14 that the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +1 has an increased light hydrocarbon conversion rate, reduced coke, and improved ethylene and propylene yields compared to the catalyst prepared by using ZSM-5 molecular sieve modified by phosphorus-containing compounds with a phosphorus valence state of +5.
Claims
1. A catalytic cracking catalyst, comprising, based on the dry weight of the catalytic cracking catalyst, 2-20 wt% of a Y-type molecular sieve, 3-80 wt% of a phosphorus-modified ZSM-5 molecular sieve, 1-70 wt% of an inorganic binder, and 2-60 wt% of clay, based on the dry weight of the catalytic cracking catalyst, characterized in that: The phosphorus-modified ZSM-5 molecular sieve has a binding energy of 134.6 to 134.7 eV in phosphorus species on the surface of the molecular sieve after hydrothermal aging at 800°C and 100% steam for 17 hours. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10-25 ppm; the inorganic binder includes a phosphorus aluminum inorganic binder and / or other inorganic binders.
2. The catalyst according to claim 1, wherein The Y-type molecular sieve is at least one selected from PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.
3. The catalyst according to claim 1, wherein The phosphorus-modified ZSM-5 molecular sieve was subjected to hydrothermal aging at 800°C and 100% steam for 17 hours and its 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 15 to 25 ppm.
4. The catalyst according to claim 1, characterized in that The phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
5. The catalyst according to claim 1, characterized in that The phosphorus-modified ZSM-5 molecular sieve is obtained by modifying a phosphorus-containing compound whose phosphorus valence state is +1.
6. The catalyst according to claim 1, characterized in that The phosphorus-modified ZSM-5 molecular sieve is obtained by contacting and impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +1, drying and calcining; or the phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding the HZSM-5 molecular sieve and a solid phosphorus-containing compound with a phosphorus valence state of +1, heating and melting the mixture, cooling it to room temperature and then calcining it.
7. The catalyst according to claim 6, characterized in that The impregnation has a water-to-screen weight ratio of 0.5 to 2 and is carried out at room temperature for 0.5 to 10 hours; the drying has an air atmosphere at 100 to 120° C. and is carried out for 2 to 24 hours; and the calcination time is 0.5 to 12 hours.
8. The catalyst according to claim 6, characterized in that The heating and melting treatment is carried out at a temperature higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates, and the treatment time is 2 to 72 hours.
9. The catalyst according to claim 6, characterized in that The phosphorus-containing compound with a phosphorus valence state of +1 is selected from one or more of hypophosphorous acid, ammonium hypophosphite, and hypophosphite; the aqueous solution of the phosphorus-containing compound with a phosphorus valence state of +1 is an aqueous solution of hypophosphorous acid adjusted to a pH value of 5-9 with ammonia water.
10. The catalyst according to claim 6, characterized in that The molar ratio of the HZSM-5 molecular sieve to the phosphorus-containing compound with a phosphorus valence state of +1 is (0.1-2.5):1, preferably (0.5-1.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum and the phosphorus-containing compound is calculated as phosphorus.
11. The catalyst according to claim 1, wherein The phosphorus-aluminum inorganic binder is 5-40% by weight based on the dry basis of the catalyst.
12. The catalyst according to claim 1, wherein The inorganic binder also contains at least one selected from pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.
13. The catalyst according to claim 1, wherein The clay is selected from at least one of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.
14. A catalytic cracking method, characterized in that: Under catalytic cracking reaction conditions, hydrocarbon oil is contacted with the catalytic cracking catalyst according to any one of claims 1 to 13 for reaction.
15. The method according to claim 14, characterized in that The catalytic cracking catalyst is used alone, or in a mixture with a conventional catalytic cracking catalyst. In the mixture, the catalytic cracking catalyst accounts for no more than 30% by weight of the total amount of the mixture, preferably 1-25% by weight, and more preferably 3-15% by weight.
16. The method according to claim 14, wherein: The catalytic cracking reaction conditions include: a reaction temperature of 500-800°C.
17. The method according to claim 14, wherein: The hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products.
Citation Information
Patent Citations
Process for producing phosphorus modified zeolite catalysts
CN103987457A
Catalytic cracking catalyst
CN114425430A
Cracking catalyst, preparation method and application
CN114425432A
Preparation method and preparation system of catalytic cracking catalyst of phosphorus-containing modified MFI structure molecular sieve
CN114762836A
Alkaline phosphate-activated clay / zeolite catalysts
US6103949A